Geochemical study on fossil vertebrates from some specific Permian and Triassic beds of the Paraná Basin (Brazil): A preliminary approach. (October 2021) - Corecco, Leonardo; Pereira, Vitor P.; Soares, Marina B.; Schultz, Cesar L.
Abstract: Access to the geochemical conditions of paleoenvironments is made through the analysis of the chemical composition of the hydroxyapatite of fossil bones. This is because the bones were able to incorporate chemical elements from adjacent fluids into their pores and channels during the fossildiagenesis process, and as a result, have their original apatite substituted. The main goal of the present study was to seek geochemical signatures in bones and related sedimentary rocks from three well-known fossiliferous units of the Paraná Basin in southern Brazil: Irati Formation, Cisuralian (three bones/rocks sampled); Rio do Rasto Formation, Guadalupian (three bones/rocks sampled) and Santa Maria Supersequence, Late Ladinian–Early Norian (nine bones/rocks sampled). Fossils and rocks were analyzed by ICP-MS. Although the Permian fossil and rock samples (from Irati + Rio do Rasto Formations) have variations among them, some geochemical parameters are common (high Be–Co–Cu–Zn–Y–W–Pb contents). This composition differentiates them from the Triassic fossils and rocks (from Santa Maria Supersequence - high contents of V–As–Ba). The P content (essential in apatite) was used to determine the degree of preservation of the studied material. The better-preserved Permian specimen has a mean = 434.19 ratio (P content of fossil bones/P content of rock) and the lowest ratio = 1.87. Within the Triassic specimens, the better preserved has ratio = 205.64 and lowest = 2.24. In Permian specimens, Y shares similar ionic radio with Ca. For Triassic specimens, Y replaces Ca and As either replaces P or is associated with minerals in bone cavities. So, Y and As substitute Ca in the analyzed material. Therefore, the Permian samples are better preserved than the Triassic ones based on their P contents; Y and As can be used as indicators to differentiate Permian fossils (high Y values) from Triassic ones (high As values). These geochemical signatures can help in forensic cases, such as robbery or illegal transport of fossils. Highlights: Characterize some specific Permian and Triassic beds of the Paraná Basin (Brazil). P contents, in fossils, can indicate its preservation degree. The fossils from Irati Formation are better preserved than those from the other units. Geochemical signatures can help in fossil's robbery or illegal transport cases.